Selection and stabilization of CD25high FOXP3+ regulatory T cells in vitro as a basis for adoptive antigen-specific immunotherapy - Wilkinson, Daniel Stephen (East Carolina University, 2017)
Autoimmune disease affects an estimated 50 million people in the United States. Autoimmune disease arises when immune tolerance is abrogated and host immune cells mount an attack against self-tissues. For example, in Multiple Sclerosis (MS) myelin-reactive CD4+ T cells coordinate an inflammatory assault directed at the myelin sheath that surrounds and protects nerve axons in the central nervous system (CNS). Currently, treatments for autoimmune diseases rely heavily on broad immunosuppression which leaves the patient open to opportunistic infections. The development of more efficacious therapeutics for autoimmune disease is imperative. CD4+ CD25+ FOXP3+ regulatory T cells (Tregs) mediate an integral role in controlling autoimmunity and chronic inflammatory disorders. The importance of Tregs is illustrated by loss-of-function mutations in the Treg-specific transcription factor gene Foxp3 that cause early-onset, fatal, multi-organ autoimmune disorders in humans and mice. Furthermore, dysfunction within the Treg compartment has been linked to numerous autoimmune diseases. Therefore, Treg-mediated suppressive activity has promise for translation as an immunotherapy for autoimmune disease and other chronic inflammatory disorders. One major hurdle preventing the advancement of Treg-based therapies is the phenotypic instability of these cells. Under inflammatory conditions, Tregs can lose FOXP3 expression and display effector T cell characteristics. In addition, Tregs are rapidly overgrown by FOXP3- conventional T cells (Tcons) in vitro in the presence of IL-2. In this study, we exploited the differential expression of the IL-2 receptor [alpha] chain (CD25) on Tregs and Tcons. Differential expression of CD25 and the consequent differences in IL-2 potency may provide a means to directly manipulate the balance of Treg and Tcon subsets in cell culture. This study is based on the hypothesis that CD25high FOXP3+ Tregs will exhibit relatively high degrees of resistance to CD25 blockade whereas CD25intermediate Tcon subsets will be fully susceptible to CD25 blockade and will selectively die due to cytokine starvation. In support of this hypothesis, the anti-mouse CD25 mAb PC61 supported the differential expansion of FOXP3+ T cells and was the key agent necessary to generate long-term, FOXP3+ Treg lines that were stable over several months of in vitro propagation. At high PC61 concentrations and low IL-2 concentrations, IL-2 dependent Treg proliferation was dominant over Tcon proliferation, and these differential growth rates enabled Tregs to progressively dominate mixed cultures. Continuously-propagated Treg lines progressively expressed "stable" Treg markers Neuropilin-1 (NRP1) and Helios (IKZF2). Treg lines were reactivated in the presence of TGF-[beta] and expanded in vitro in the presence of PC61 without showing any decrease in FOXP3 expression as a percentage of the T cell population or on a per cell basis. The ability to propagate Tregs in culture for extended periods of time allowed for in depth analysis of various Treg characteristics. Long-term propagated Tregs retained suppressive capabilities as shown by in vitro suppression assays. Additionally, Tregs mediated infectious tolerance by conferring FOXP3 expression in naïve FOXP3- T cells. Importantly, myelin oligodendrocyte glycoprotein (MOG)-specific Tregs had in vivo inhibitory activity as shown by adoptive transfer of suppression in the C57BL/6 model of experimental autoimmune encephalomyelitis (EAE). These studies provide key tools for stabilizing Tregs in vitro, offer insight into Treg mechanisms of suppression, and provide a basis for Treg adoptive immunotherapies.
Keywords: Rodent; FOXP3; EAE/MS; Tolerance; Neuroimmunology; T-Lymphocytes, Regulatory; Immunotherapy, Adoptive